2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--27889
|View full text |Cite
|
Sign up to set email alerts
|

Board # 60: Learning to Make Change by Revolutionizing Departments: Initial Team Experiences

Abstract: Ella L. Ingram is an Associate Professor of Biology and Director of the Center for the Practice and Scholarship of Education at Rose-Hulman Institute of Technology. Her educational research interests include promoting successful change practice of STEM faculty, effective evolution and ecology instruction, and facilitating undergraduate research experiences. Her teaching portfolio includes courses on: nutrition, introductory biology, ecology and environmental studies, evolution, evolutionary medicine, and resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…Unlike the NSF-funded study (Ingram, Litzler, Margherio, & Williams, 2017), there was no need to re-negotiate the promises they made grantors. Nevertheless, this FLC still had to set boundaries for the discussion and create a vision for itself.…”
Section: Faculty Learning Communitiesmentioning
confidence: 99%
“…Unlike the NSF-funded study (Ingram, Litzler, Margherio, & Williams, 2017), there was no need to re-negotiate the promises they made grantors. Nevertheless, this FLC still had to set boundaries for the discussion and create a vision for itself.…”
Section: Faculty Learning Communitiesmentioning
confidence: 99%
“…From the research side, one of the recent findings is that many teams utilized informational communication, in which change leaders provide details about plans and goals, essentially offering a proposition for faculty to join or resist. In contrast, formational communication empowers faculty or other stakeholders to contribute to the change process, offering alternative or additional ideas for goals or how to implement the change, and this can have strong effects on the extent to which teams can move forward with their change projects [14,17]. This research finding is completely obvious in retrospect, but neither practitioner would have captured the strength and importance of this outcome without the qualitative data to back it up.…”
Section: Outcomes Of the Redpar Partnershipmentioning
confidence: 90%
“…We have engaged in a wide variety of outreach and dissemination efforts, both with the partners as coauthors and with individual members representing the partnership and assuming authorship credit. We have produced both individual and joint publications and presentations and shared our work across platforms [e.g., 13,14,15,16]. For example, we identified that effective communication was a challenge for change teams; they were communicating with multiple stakeholders, all requiring different parts of the story, and confusion resulted among stakeholders.…”
Section: Outcomes Of the Redpar Partnershipmentioning
confidence: 99%
“…It also includes how we disseminate the research and practice work that is the foundation of our project. Specifically, we have considered with care the various channels for communication and the modes of conveying our work that are at our disposal, such as conferences like ASEE and research journals like Journal of Engineering Education [1], [2], [3]. These two examples represent typical forms of communication that are accepted within the engineering education community, but both require extended time frames in order to reach their intended audiences.…”
Section: Introductionmentioning
confidence: 99%
“…As a mode that supports both research and practice, the tipsheet accomplishes several important goals. First, the content is drawn from both the research conducted with the RED teams and the practitioners' work with the teams on specific skill sets considered important tools for change makers [1], [2], [3]. Each tipsheet takes up a single theme and grounds the theme in the research we have conducted while offering practical tips for applying the information.…”
Section: Introductionmentioning
confidence: 99%